2020
DOI: 10.20517/2394-4722.2020.70
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting the relevance of CA 19-9 in pancreatic cancer

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is currently the fourth most common cause of cancer-related deaths in the United States. It has a poor prognosis and remains a difficulty to treat malignancy. Over the past several decades, significant efforts have been directed towards developing new approaches to enhance the efficacy of therapeutic regimens for PDAC treatment. In recent years, the measurement of serum carbohydrate antigen 19-9 (CA 19-9) has become one of the most validated and extensively used tumour b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…In normal pancreatic tissue, protein glycosylation produces end-products, which function as a lubricant for pancreatic ducts. However, an aberrant process occurs in cancer tissues, leading to the production of CA 19-9 [ 6 ]. Currently, CA 19-9 or Sla are the only tumor markers approved by the Food and Drug Administration (FDA) in the United States to support the diagnosis of pancreatic cancer [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…In normal pancreatic tissue, protein glycosylation produces end-products, which function as a lubricant for pancreatic ducts. However, an aberrant process occurs in cancer tissues, leading to the production of CA 19-9 [ 6 ]. Currently, CA 19-9 or Sla are the only tumor markers approved by the Food and Drug Administration (FDA) in the United States to support the diagnosis of pancreatic cancer [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tumoral biomarkers' relevance in diagnosis, prognosis, and surgical decision-making processes is still a matter of debate ( 29 , 30 ). Ca 19-9 it's one of the most studied; Santucci et al ( 31 , 32 ), found that major levels of CA 19-9 in patients with locally advanced pancreatic cancer or metastatic disease compared with those with resectable disease; however, limitations among the use of CA 19-9 in clinical practice includes that almost 50% of patients with tumors < 2 cm do not elevate any tumoral biomarker and for that reason, currently there is still a lack of evidence in terms of prognosis ( 30 ). Our study did not find any statistical difference between CA 19-9 levels in patients with positive HLA compared with the negative group.…”
Section: Discussionmentioning
confidence: 99%
“…Current diagnostic methods and clinical biomarkers, such as serum carbohydrate antigen 19-9 (CA19-9)—the gold standard biomarker for PDAC diagnosis and the only diagnostic serum marker approved by the Food and Drug Administration (FDA) for pancreatic cancer– are limited in their capacity to accurately detect early-stage PDAC. This is because ~7% of the population do not express the antigen and the high occurrence of false positives and non-specific expression of CA19-9 compromise the differential diagnosis between malignant adenocarcinomas and benign pancreato-biliary pathologies, including chronic pancreatitis (CP), cholangitis and obstructive jaundice [ 126 , 127 , 128 , 129 ]. As such, CA19-9 is generally supported for the assessment of recurrence or survival after curative resection, rather than an initial or early-stage diagnostic screening [ 130 , 131 , 132 ].…”
Section: Clinical Evidence Supporting Upas Overexpression In Pancreat...mentioning
confidence: 99%